KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE SQ3R TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA SMP KELAS VII - Firmansyah, Dian Teguh; Zaenuri, Zaenuri; Mulyono, Mulyono (Department of Mathematics, Universitas Negeri Semarang, 2012)
This study aims to determine the effectiveness of cooperative learning model types Survey Question Read Recite Review (SQ3R) to mathematical problem solving abilities of students in the junior high school grade VII of material relationships between angles. The population in this study is students of grade VII SMP N 1 Pagerbarang school year 2011/2012. The samples taken by cluster random sampling technique so namely studentsinclassVIIB as control group and studentsinclass VIIC as experiment group. Design used in this research is true experimental design posttest only control type. Results showed that the averagetest scores mathematical problem solving abilities of students in class taught by cooperative learning model types SQ3Rof material relationships between angles achieve minimal completeness criteria(KKM) applies in SMP N 1 Pagerbarang, with many students who achieve KKM is more than equal 75%, and average test scores mathematical problem solving abilities of students in classtaught by cooperative learning model typesSQ3Rof material relationships between anglesmore than the average test scoresmathematical problem solving abilities of students in class taught by expository model. Based on the research results can be concluded that the cooperative learning model types SQ3R is effective to improve students problem solving skills students grade VII to the material relationships between angles.